Isolasi dan Respons Tumbuh Cendawan Mutualistik Akar pada Beberapa Tanaman Pangan dan Kehutanan - Nampiah Sukarno; Utut Widyastuti Suharsono†; Yasuyuki Hashidoko†; Rida Oktorida Khastini (Jurnal Ilmu Pertanian Indonesia, 2022)
The study aims to isolate and test the effectiveness of mutualistic root symbiont fungi isolates from the roots of rubber plants grown in marginal acidic soil plantations in increasing the growth of food crops and forestry plants. The fungal were isolated by root surface sterilization methods. We obtained 19 fungal isolates consisting of 8 genera, namely Alternaria, Aspergillus, Cladosporium, Curvularia, Fusarium, Penicillium Paecilomyces, Trichoderma, and mycelia sterilia. All isolates were subjected to a pathogenicity test on the Centrosema pubescens plant. Five out of the 19 fungal isolates increased plant growth and showed no disease symptoms, and the Aspergillus section Nigri FKK 3 isolate showed the best response. The isolate was further analyzed to assess the growth response of food crops (rice and corn) and forestry plants (Acacia auriculiformis and Paraserianthes falcataria). The treatments consisted of 3 phosphate (P) concentrations, namely 20%, 50%, and 100% of the recommended field applications. The combination of mutualistic fungal inoculation of Aspergillus section Nigri FKK 3 and 50% P concentration exhibited the highest biomass growth response compared to other treatments. This finding can provide basic information for developing fungal-based fertilizers to increase the productivity of food crops and forestry plants on sub-optimal land. Keywords: food crops, phosphate fertilizer, forestry trees, plant growth improvement, root mutualistic fungi